Evaluation of mobile eye tracking for forensic analysis of pedestrian falls. (September 2013) - Kuzel, Michael; Cohen, H. Harvey; Rauschenberger, Robert; Cohen, Joseph
The forensic analysis of falls is most commonly reliant on the application of generalized non-case specific research to support whether a person would be likely to gaze in the direction or area of a hazard prior to a fall event. The recent developments of mobile eye tracking systems may allow for direct, on-site evaluations, to assess probability of detection of claimed hazardous conditions. Herein, an evaluation of a mobile eye tracking system is provided based on the application to a forensic case study that involved a transition from one space to another through a door. The results of the initial study were further evaluated in three other areas, with similar settings. The results of two studies demonstrate support for the hypothesis that a person would not look down at the landing area when stepping. However, in achieving these results, we found both support for the utility of the device as well as certain limitations for future use.